DAMPAK KENAIKAN BBM TERHADAP BEBAN PENGELUARAN BIAYA PARA PEKERJA DARI TIGA PROFESI DI MASA COVID-19 - Endro Tri Susdarwono (Business Journal : Jurnal Bisnis Dan Sosial, 2023)
This study aims to analyze the expenses incurred by workers from three work sectors or professions after the increase in fuel prices. The survey conducted in this study was aimed at finding out the amount of money they had to incur in order to meet food and shelter needs in the 10-day period after the increase in fuel prices. The method used in this study is quantitative analysis with a descriptive statistical approach, namely describing the data and testing the hypothesis on the sign and the Kruskall-Wallis method. The results of the study stated that based on testing the hypothesis on the sign that the increase in fuel prices determined by the government had an impact on household expenses including food and housing costs from the three work or professional sectors. Based on the results of the survey answers given by respondents, 58.62 percent said that the policies taken by the government to increase fuel prices had an impact on household expenses, while 41.38 percent had no impact. It is possible that 41.38 percent of the respondents received the BBM Direct Cash Assistance provided by the Government. Meanwhile, from the research hypothesis of the Kruskall-Wallis method, it is stated that workers from the three sectors of work or profession bear the same burden in terms of expenditure or consumption for food and housing after 10 days of the increase in fuel prices. So it was concluded that the three actors in the three work sectors were directly affected by the increase in fuel prices imposed by the Government through the burden of increasing spending costs to meet food and shelter needs.